Learning, unlearning, relearning: Strategies for 21st century learners to tackle the digital learning paradox - Verma, Vaibhav; Babu M, Sameer (Journal of Interdisciplinary Studies in Education, 2026)
The 21st century faces a digital learning paradox where an abundance of information leads to cognitive overload. This paper examines strategies for the learning cycle of learning-unlearning-relearning and emphasizes the need for cognitive flexibility in a fast-paced digital landscape. Using Braun and Clarke's thematic analysis, it identifies key themes, including psychological barriers to unlearning and the transformative potential of AI in education. Findings indicate that while digital tools enhance accessibility, they may result in shallow processing and decreased retention. The research proposes solutions such as categorizing knowledge and encouraging metacognition to foster lifelong learning in institutional settings. Additionally, a conceptual framework for adaptive learning is presented, advocating for skill-based pedagogies over traditional content-focused approaches.